Effect of Doping Cu on the Structural and Optical Properties of (CdTe) Thin Films - Maki, Samir A.; Hasson, Bushra K.; Feyad, Salam H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research we studied  the structural and optical properties of (CdTe) thin films which have been prepared  by thermal evaporation deposition method on the glass substrate at R.T with thickness (450 ï‚± 25) nm., as  a function of doping  ratio with copper element  in (1,3,5) % rate .The structure  measurement  by X-ray diffraction (XRD) analyses shows that the single phase of (CdTe) with polycrystalline structure with a preferred orientation [111].   The optical  measurement shows that the (CdTe) films have a direct energy gap, and they decrease with the increase of doping ratio reaching to 5% . The optical constants are investigated and calculated, such as absorption coefficient (Î±), refractive index (n) , extinction coefficient (k) and the dielectric constants (Ð„)  with both parts  real and imaginary  for the  wavelengths in the range (300-1100) nm, before and after doping processes